2009
DOI: 10.1111/j.1530-2415.2009.01193.x
|View full text |Cite
|
Sign up to set email alerts
|

Taking a “Hands On” Approach to Diversity in Higher Education: A Critical‐Dialogic Model for Effective Intergroup Interaction

Abstract: This article reviews divergent empirical evidence on interracial contact. While research on diversity in higher education provides ample evidence for the educational benefits of engaging with diversity in informal interactions or courses, experimental and naturalistic studies in social psychology on interracial interactions reveal a complicated picture, showing what appear to be both positive and negative effects. Rather than addressing the question of whether or not to promote interracial interactions on camp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 50 publications
6
78
0
Order By: Relevance
“…They are also consistent with previous studies on motivation to bridge difference and studies examining a broader set of democratic outcomes (Gurin, Nagda, and Lopez, 2004;Nagda, 2006;Nagda and Zúñiga, 2003). Further results demonstrate that a number of dialogue effects, based on longitudinal survey data, persist up to one year later (Sorensen, Nagda, Gurin, and Maxwell, 2009). …”
Section: Educational Benefits For Studentssupporting
confidence: 86%
“…They are also consistent with previous studies on motivation to bridge difference and studies examining a broader set of democratic outcomes (Gurin, Nagda, and Lopez, 2004;Nagda, 2006;Nagda and Zúñiga, 2003). Further results demonstrate that a number of dialogue effects, based on longitudinal survey data, persist up to one year later (Sorensen, Nagda, Gurin, and Maxwell, 2009). …”
Section: Educational Benefits For Studentssupporting
confidence: 86%
“…Sociocultural theory (Bakhtin, 1986;Vygotsky, 1978;Wells, 1999aWells, , 1999bWells, , 2007Wells, , 2009, intergroup dialogue 3 (Nagda & Gurin, 2007;Sorensen, Nagda, Gurin, & Maxwell, 2009), and critical consciousness (Freire, 1999) are complementary views of learning that inform my understanding and use of CDM. Although they are theoretically and methodologically distinct, each lens emphasizes dialogical meaning-making that attends to the role of power in knowledge production and social life.…”
Section: Features Of a Critical And Dialogical Modelmentioning
confidence: 99%
“…What this means is that I use CDM as a pedagogical framework to facilitate shared meaning-making wherein "dialogue as a process of learning and knowing must always involve a political project with the objective of dismantling oppressive structures and mechanisms prevalent both in education and society" (Freire & Macedo, 1995, p. 380). In total, I draw on views of learning from sociocultural theory, intergroup dialogue, and critical consciousness to facilitate content learning and structured interaction that encourages students to understand content through guided self-reflection, critical communication and alliance building (Sorensen et al, 2009). …”
Section: Features Of a Critical And Dialogical Modelmentioning
confidence: 99%
“…One way to leverage the power of interpersonal interaction to help develop multicultural competence would be to better recruit PSTs with more diverse experiences and viewpoints (Sleeter, 2001;Villegas & Lucas, 2004). While impossible to ensure, creating a more racially, ethnically, culturally, gender, and regionally diverse student body and crafting opportunities for true interpersonal interaction and cooperation can give education schools a better probability of having students develop first-hand the skills and dispositions to embrace diversity and understand and value inclusive environments (Sorensen et al, 2009). Lastly, providing varied, diverse, and immersive teacher field experiences may lead to better multicultural outcomes building upon principles mentioned earlier (Pohan, Ward, Kouzekanani, & Boatright, 2009;.…”
Section: Discussionmentioning
confidence: 99%
“…Research using the contact hypothesis has found that settings that provide optimal conditions for intergroup interaction (i.e., interdependence and cooperation between groups, institutional support, and common goals across groups) will result in reduced prejudice, more positive attitudes, and increased confidence and comfort to have interactions with others from different groups (Hurtado, 2005;Sorensen, Nagda, Gurin, & Maxwell, 2009). Having actual history and familiarity with cross-racial/ethnic interaction can allow PSTs to structure their diverse classrooms and prepare their students for intergroup contact, rather than relying on lay theory and curricular platitudes (Fitchett et al, 2012;Keengwe, 2010).…”
Section: Personal and Interpersonal Influences Of Multicultural Compementioning
confidence: 99%